2018
DOI: 10.3390/ijms19010305
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility with Panax notoginseng and Rehmannia glutinosa Alleviates the Hepatotoxicity and Nephrotoxicity of Tripterygium wilfordii via Modulating the Pharmacokinetics of Triptolide

Abstract: Tripterygium wilfordii (TW) and the representative active component triptolide show positive therapeutic effect on the autoimmune disorders and simultaneously ineluctable hepatotoxicity and nephrotoxicity. Combinational application of Panax notoginseng (PN) and Rehmannia glutinosa (RG) weakens the toxicity of TW according the clinical application of traditional Chinese medicine. This article was aimed at the mechanism of decreasing toxicity of TW by the combinational application of PN and RG. Biochemical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…A study (which included 428 trials) published in 2016 reported that the incidence of all grades of AEs caused by TwHF preparations was 26.7% [95% CI (24.8–28.8)]. The results of that systematic review were similar to our findings, but it included all types of TwHF preparations and 94% (402/428) of the included trials were from Chinese databases (Zhang et al, 2018). The use of all types of TwHF preparations might increase statistical heterogeneity, and literatures of low quality might lead to low quality of methodology.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study (which included 428 trials) published in 2016 reported that the incidence of all grades of AEs caused by TwHF preparations was 26.7% [95% CI (24.8–28.8)]. The results of that systematic review were similar to our findings, but it included all types of TwHF preparations and 94% (402/428) of the included trials were from Chinese databases (Zhang et al, 2018). The use of all types of TwHF preparations might increase statistical heterogeneity, and literatures of low quality might lead to low quality of methodology.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that the AEs caused by TWP mainly include leukopenia, gastrointestinal reactions, menstrual disorders, and liver dysfunction (Zhang et al, 2016). Incidences of leukopenia and liver dysfunction have significantly increased in patients treated for immune system disease, and independent incidences of AEs caused by TwHF have been associated with various organ toxicities, such as intestinal toxicity, reproductive toxicity, hepatotoxicity, nephrotoxicity, hematotoxicity, and cutaneous toxicity (Liu et al, 2018; Zhang et al, 2018). This indicates that the therapeutic dose of TwHF is close to its toxic dose, resulting in unavoidable occurrence of AEs.…”
Section: Introductionmentioning
confidence: 99%
“…Lists of herbs and concoctions that were hepatotoxic or hepatoprotective, their respective causality levels, and number of cases are compiled in Tables 1 to 5. 9,13-46…”
Section: Resultsmentioning
confidence: 99%
“…When prejaundill occurs. Clinical symptoms of TP-induced liver injuries include jaundice ( Xue et al, 2009 ), and Zhang et al (2018) found that tripterygium wilfordii significantly increased the total bilirubin in rat serum, which may be related to the changes in transporter expressions.…”
Section: Discussionmentioning
confidence: 99%